ESTIMASI HERITABILITAS DAN RESPONS SELEKSI IKAN NILA HITAM (Oreochromis niloticus) DI TAMBAK - Adam Robisalmi (BERITA BIOLOGI, 2019)
Genetic improvement in the establishment of a rapid growth strain of Nile tilapia might be achieved through selective breeding program This research was aimed to estimate heritability and response selection of nile tilapia in brackishwater pond. Breeding  activity was carried out in fresh water in hapa 2x1x1 m. Males and females were breeding in pairs with a ratio of 1: 1. The number of established families was 19 families of 50 broodstock pairs. Harvesting of larvae was done on day 14. Larvae were collected and then kept in net 2 x 2 x1 m  with stocking density 125 fish/m2 for 60 days. The next stage was sexing  by grouping the male and female populations in each family. Grow out was carried out in net cage (3 x 5 x1.5 m ) that were placed in brackiswater pond at salinity 25–30 g/L with density 10 fish/m2.  Selection of broodstock in the male and female populations was done on weight of 250–300 g. Cut off selection was determined on weight from 316 to 382g (male) and 221–315 g (female). The results of this study showed that the estimation value for heritability of male and female were 0.42 ± 0.22 and 0.42 ± 0.23 and the estimation value for response selection were 10.66% (male) and 10.92% (female).